The Development of Prototype Data Delivery System Based on LoRa and Mesh Topology - Dewa Gede Kesuma Yoga; I Made Agus Dwi Suarjaya; I Putu Agus Eka Pratama (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2022)
This study aimed to build a prototype development on a data transmission system using the LoRa communication protocol by applying a mesh topology in areas that difficult to reach by Wi-Fi or internet networks, the position of the first IoT devices has a role as a gateway between the IoT devices and a server. To connect the IoT devices with a server, the location of the IoT devices must be in a strategic location therefore it can connect to the internet network. Then the second IoT devices has a role as a gateway between the IoT devices. This study emphasizes the use of a WEB interface application on a computer or laptop used by the user to control and monitor the condition of an electronic device that has a considerable distance. This study used the NodeMCU ESP8266 microcontroller which is used on the first IoT devices, then this study also used the Arduino UNO microcontroller which is used on every IoT device which is intended to carry out the process of sending data between IoT devices. The used of the LoRa module in this study was used as a communication medium between IoT devices, and the use of the DS18B20 temperature sensor was used as a data transmission parameter. Based on the trials that have been carried out, the results of the prototype system work well according to the available features, but there is still one obstacle in this study where the IoT device in carrying out the data transmission process will be disrupted if there is another device that has a frequency that resembles the IoT device used. and there are obstacles in the form of buildings or dense trees, resulting in disturbances in sending data. This IoT device can still be used to send data even though there are obstacles as previously mentioned, provided that the distance does not exceed 500 meters. Keywords: Arduino Uno, IoT, NodeMCU